Best practice standards for the delivery of NHS infection services in the United Kingdom. (November 2021) - Ratnaraja, Natasha V.D.V.; Davies, Angharad P.; Atkins, Bridget L.; Dhillon, Rishi; Mahida, Nikunj; Moses, Samuel; Herman, Joanne; Checkley, Anna; Partridge, David; Llewelyn, Martin J.
Highlights: This is the first published set of standards for an infection service in the UK. It incorporates all key elements of an infection service. There are recommended PA ranges for key specialist roles. These are evidence based where possible or based on specialist expertise. Written by the BIA and endorsed by RCP and RCPath. Abstract: Infection expertise in the NHS has historically been provided predominantly by hospital-based medical microbiologists responsible for provision of diagnostic services and advice to front-line clinicians. While most hospitals had consultant-led microbiology departments, infectious iiseases departments were based in a small number of specialist centres. The demand for infection expertise is growing in the NHS, driven by advances in medical care, increasing awareness of the impact of antibiotic resistant and healthcare associated infections and threats from emerging infectious diseases. At the same time diagnostic services are being reorganised into pathology networks. The Combined Infection Training (CIT) is delivering a consultant workforce with expertise both in laboratory diagnostic practice and delivery of direct patient care. These changes create challenges for delivery of high quality infection expertise equitably across the NHS. They also offer an opportunity to shape infection services to meet clinical and laboratory demands. To date there has not been an attempt to bring together a single set of best practice guidelines for the requirements of an infection service. This document sets out seven standards. These are written to be practical and flexible according to the diverse ways in which infection expertise may be required across the NHS. It has been prepared by the Clinical Services Committee of the British Infection Association drawing on published evidence and guidance where they exist and on the group's extensive experience of delivering infection services in hospitals across the NHS. It was then refined with input from the RCP Joint Specialist committee (JSC) and the RCPath Specialist Advisory Committee (SAC) and through consultation with the RCPath membership. It has been endorsed by the Royal College of Pathologists and the Royal College of Physicians. It will be reviewed annually by the CSC and updated as additional evidence becomes available.